2014
DOI: 10.1002/tcr.201300040
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chiral Catalysts for Mukaiyama Aldol Reactions in Aqueous Media

Abstract: Since the discovery of the Mukaiyama aldol reaction in 1973, tremendous efforts have been made to develop a definitive catalyst that catalyzes asymmetric Mukaiyama aldol reactions under mild conditions with broad substrate tolerance. Forty years later, an exhaustive search for a water-compatible Lewis acid was able to uncover the hidden potential of iron(II) and bismuth(III), leading to the establishment of broadly applicable and versatile catalytic systems for asymmetric Mukaiyama aldol reactions in aqueous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The catalytic ability of Fe­(II) and Fe­(III) was also compared; the reaction with Fe­(III) gives rise to very low yield (15%) and poor enantioselectivity (1% ee) . The diastereoselectivity of the reaction is however independent of the oxidation state of Fe . Ollevier et al also reported a similar trend for the Mukaiyama aldol reaction catalyzed by Fe­(III) perchlorate system (25% yield and 52% ee) …”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…The catalytic ability of Fe­(II) and Fe­(III) was also compared; the reaction with Fe­(III) gives rise to very low yield (15%) and poor enantioselectivity (1% ee) . The diastereoselectivity of the reaction is however independent of the oxidation state of Fe . Ollevier et al also reported a similar trend for the Mukaiyama aldol reaction catalyzed by Fe­(III) perchlorate system (25% yield and 52% ee) …”
Section: Introductionmentioning
confidence: 66%
“…Kitanosono et al have studied the ESI-MS spectra under the reaction conditions, and several Fe­(II) complexes, such as [(L1)­Fe­(OTf)] + and [(L1)­Fe­(DME) (OTf)] + , were observed. The catalytic ability of Fe­(II) and Fe­(III) was also compared; the reaction with Fe­(III) gives rise to very low yield (15%) and poor enantioselectivity (1% ee) . The diastereoselectivity of the reaction is however independent of the oxidation state of Fe .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We hypothesized that the addition of an organic acid might catalyze the enamine formation more effectively, 32–34 so we added chloroacetic acid (10 mol%) (Table 1, entries 13–18). We observed the best results when chloroacetic acid (10 mol%) and 10 equivalents of water are added (Table 1, entries 19–24), enhancing yields (83%–98%) and improving enantioselectivities (73%–90%).…”
Section: Resultsmentioning
confidence: 99%
“…Fe is an abundant, inexpensive, and nontoxic transition metal, and therefore, the development of Fe-based complexes for efficient and highly selective carbon–carbon bond formation reactions becomes critical. In this direction, the Mukaiyama aldol reaction is very useful. We used DFT and AFIR methods to understand the mechanism and the selectivity of the aqueous Mukaiyama aldol reaction catalyzed by an Fe-based chiral complex (Figure a) …”
Section: Transition Metal Catalysismentioning
confidence: 99%